A method for preparing moisture-proof and wear-resistant PVC floor

By introducing composite modification additives into PVC floors, a tightly-bonded system is formed, which solves the problem of low wear resistance of existing PVC floors, achieves higher wear resistance and moisture resistance, and extends service life.

CN118546479BActive Publication Date: 2025-02-18JIANGSU ZHONGXIN HOME NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410721946.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-05
Publication Date
2025-02-18
Estimated Expiration
2044-06-05

AI Technical Summary

Technical Problem

The wear resistance of existing PVC floors is low, which leads to easy wear and tear after long-term use, and the surface is uneven, affecting service life.

Method used

By introducing composite modification additives into the raw material components of PVC floor, including hemicellulose waste alkali liquid, modified concave and convex rod soil, nano silica and silicon carbide, etc., it is subjected to stirring, ultrasonic dispersion and reaction treatment to form a tight The combined system improves the wear resistance of PVC floors.

Benefits of technology

The wear resistance and moisture resistance of PVC floors are significantly improved, the service life is extended, and the use of modification additives is used to avoid the problem of poor bonding of conventional inorganic fillers in the polyvinyl chloride system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118546479B_ABST
    Figure CN118546479B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a moisture-proof and wear-resistant PVC floor, which relates to the technical field of PVC floor, and comprises the following steps: (1) preparing materials: weighing raw material components: PVC resin, plasticizer, stabilizer, carbon black, composite modification auxiliary agent, stone powder; (2) mixing materials; (3) banburying: adding the obtained mixture into a banbury mixer for banburying treatment to obtain a banburying material; (4) tableting; (5) post-treatment. The invention significantly improves the raw material components of the PVC floor, introduces new raw material components and coordinates the dosage of each component, so that the prepared PVC floor has excellent wear resistance and moisture resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of PVC flooring, in particular to a method for preparing a moisture-proof and wear-resistant PVC flooring. Background Art

[0002] PVC flooring is a new type of lightweight floor decoration material that is widely popular nowadays. It is also called "lightweight flooring". PVC flooring uses PVC resin as the main raw material, with fillers, plasticizers, stabilizers, colorants and other auxiliary materials added. It is produced on a sheet substrate through coating, calendering, extrusion or extrusion processes.

[0003] PVC flooring is becoming a better choice for floor materials because of its green and environmentally friendly features and excellent performance. It is increasingly replacing traditional ceramic tiles and wooden floors.

[0004] PVC flooring has a wide range of applications and can be used in various indoor places such as homes, hospitals, schools, office buildings, factories, supermarkets, businesses, stadiums, etc.

[0005] Prior art disclosure (announcement) number: CN102345368A, semi-flexible PVC flooring discloses: "The present invention belongs to PVC flooring, and particularly relates to semi-flexible PVC flooring. A semi-flexible PVC flooring, characterized in that it is composed of the following formula, which is formulated by weight: 100-110 parts of PVC, 25-30 parts of kaolin, 600-620 parts of calcium carbonate, 25-30 parts of DOP, 3-5 parts of zinc stearate, and 3-5 parts of Ba-Cd-Zn composite stabilizer. The present invention provides a new type of semi-flexible PVC flooring, which has the functions of fire prevention, scratch resistance, moisture resistance, etc., to meet people's growing needs." However, its wear resistance is relatively general. The low wear resistance will cause the PVC floor to be continuously worn after a long period of use, thereby causing the surface of the PVC floor to become uneven, affecting the subsequent normal use, and causing the service life to be significantly shortened.

[0006] Based on this, a method for preparing a moisture-proof and wear-resistant PVC floor is provided to solve the existing technical problems. Summary of the invention

[0007] The purpose of the invention is to provide a method for preparing a moisture-proof and wear-resistant PVC floor to solve the deficiencies in the prior art.

[0008] The technical solution adopted by the present invention is as follows:

[0009] A method for preparing a moisture-proof and wear-resistant PVC floor comprises the following steps:

[0010] (1) Material preparation: weigh the raw material components: PVC resin, plasticizer, stabilizer, carbon black, composite modification additive, and stone powder;

[0011] (2) Mixing: First, add PVC resin, plasticizer, stabilizer, carbon black, and composite modification additive to a mixer in sequence, stir and mix for 30 minutes, then add stone powder, and continue mixing for 30 minutes to obtain a mixture;

[0012] (3) Banburying: adding the mixed material obtained above into a banbury mixer for banburying treatment to obtain a banburying material;

[0013] Among them, the internal mixing temperature is 200℃;

[0014] The mixing time is 20-25 minutes;

[0015] (4) Sheeting: Add the mixed material to the calender and press it into a base sheet, and then press the color film onto the base sheet through a press to form a semi-finished product;

[0016] (5) Post-processing: The semi-finished products are subjected to curing, edge punching, laminating, quality inspection, packaging, palletizing and storage.

[0017] As a further technical solution, the raw material components in step (1) include, by weight: 60-68 parts of PVC resin, 5-6 parts of plasticizer, 1-3 parts of stabilizer, 6-8 parts of carbon black powder, 10-15 parts of composite modification additive, and 78-85 parts of stone powder.

[0018] As a further technical solution, the preparation method of the composite modification auxiliary agent in step (1) is:

[0019] Firstly, hemicellulose waste alkali liquor, deionized water, modified attapulgite, nano-silicon dioxide and silicon carbide were added to a reactor in sequence, stirred at 500 r / min for 30 min at room temperature, and then ultrasonically dispersed for 1 min to obtain a dispersed mixed solution;

[0020] Sodium bisulfite was added to the dispersed mixed solution obtained above, and the mixture was stirred for reaction for 40 minutes. The reaction temperature was adjusted to 75° C. After the reaction was completed, the mixture was kept warm for 15 minutes to obtain an intermediate solution.

[0021] Add ammonium persulfate to the intermediate solution obtained above, wherein the molar ratio of ammonium persulfate to sodium bisulfite is 1:1, adjust the temperature to 70° C., and stir and react for 40 minutes to obtain a second intermediate solution;

[0022] Adding a mixed solution of n-butyl acrylate and N,N-methylenebisacrylamide dropwise to the second intermediate solution, stirring and reacting for 2 hours, and then filtering to obtain a reaction mixture;

[0023] The reaction mixture is washed with anhydrous ethanol, and then placed in a drying oven for drying to obtain a composite modified auxiliary agent;

[0024] The drying temperature is 60°C and the drying time is 15 hours;

[0025] As a further technical solution, the mixing ratio of the hemicellulose waste alkali solution, deionized water, modified attapulgite, nano-silicon dioxide, and silicon carbide is 120 mL: 200 mL: 30-35 g: 5-8 g: 1-1.5 g;

[0026] The hemicellulose concentration is 85 g / L, and the alkali concentration is 28.2 g / L;

[0027] The mixing ratio of the dispersed mixed liquid and sodium bisulfite is 100mL: 1-2g;

[0028] The mass fraction of n-butyl acrylate in the mixed solution of n-butyl acrylate and N,N-methylenebisacrylamide is 10%;

[0029] The mass fraction of N,N-methylenebisacrylamide is 3%;

[0030] The volume ratio of the second intermediate liquid, n-butyl acrylate and N,N-methylenebisacrylamide mixed liquid is 10:1-1.2.

[0031] As a further technical solution, the modified attapulgite preparation method is:

[0032] The attapulgite and the acid treatment solution were mixed, the temperature was adjusted to 80°C, the mixture was stirred for 2 hours, and then allowed to stand for 4 hours, and then filtered, washed with deionized water until neutral, and dried in a drying oven to obtain pretreated attapulgite;

[0033] The pretreated attapulgite was treated with microwaves for 10-15 minutes and naturally cooled to room temperature to obtain modified attapulgite.

[0034] As a further technical solution, the acid treatment solution is a sulfuric acid solution;

[0035] The concentration of the sulfuric acid solution is 2 mol / L;

[0036] The mixing ratio of attapulgite and sulfuric acid solution is 12-16g:200mL.

[0037] As a further technical solution, the microwave power is 550W.

[0038] As a further technical solution, the plasticizer is phthalate.

[0039] As a further technical solution, the stabilizer is a Ca / Zn stabilizer.

[0040] As a further technical solution, the curing time is 28-30 hours and the temperature is 25°C.

[0041] Beneficial effects:

[0042] The invention significantly improves the raw material components of the PVC floor, introduces new raw material components and matches the dosage of each component, so that the manufactured PVC floor has excellent wear resistance and moisture resistance.

[0043] In the prior art, conventional inorganic fillers are introduced to improve the wear resistance of PVC floors. However, since conventional inorganic fillers have relatively weak interface bonding performance with polyvinyl chloride, certain gaps will be generated during bonding treatment within the polyvinyl chloride system, which will significantly reduce the wear resistance of the manufactured PVC floors. In addition, water is easily retained, reducing the moisture-proof performance of the PVC floors. The present invention obtains a composite modified additive through a series of treatments, which can be tightly bonded with polyvinyl chloride, thereby significantly improving the wear resistance of the PVC floor.

[0044] The PVC floor prepared by the present invention mainly uses PVC as a basic component, and a certain amount of composite modification additive is added to assist PVC in combining various components together to form a stable system. Stone powder, carbon black, and composite modification additive are all wear-resistant structures and can be evenly dispersed in the PVC floor system, so that the PVC floor can have uniform and stable wear resistance, thereby improving its service life.

[0045] By introducing composite modification additives into PVC flooring, the physical properties of PVC flooring can be improved. The silica in the composite modification additive can not only increase the hardness of PVC flooring and further improve its wear resistance, but also has strong antioxidant properties, which can effectively prevent aging and deterioration of PVC flooring and increase the service life of PVC flooring.

[0046] The use of plasticizer can improve the overall strength. Together with the effect of the composite modification additive, it not only improves the compatibility and cross-linking degree and the wear resistance in the PVC floor system, but also significantly improves the mechanical properties of the PVC floor. If the composite modification additive prepared by the present invention is lacking, the cohesion of the PVC floor system will be significantly reduced, and the wear resistance and mechanical strength will be reduced to varying degrees. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 The present invention is a flow chart of a method for preparing moisture-proof and wear-resistant PVC floor;

[0048] Figure 2 It is a bar graph of tensile strength of samples of embodiments and comparative examples. DETAILED DESCRIPTION

[0049] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] The following are specific embodiments:

[0051] Example 1

[0052] A method for preparing a moisture-proof and wear-resistant PVC floor comprises the following steps:

[0053] (1) Material preparation: weigh the raw material components by weight, including: 60 parts of PVC resin, 5 parts of phthalate, 1 part of Ca / Zn stabilizer, 6 parts of carbon black powder, 10 parts of composite modification additive, and 78 parts of stone powder;

[0054] (2) Mixing: First, add PVC resin, plasticizer, stabilizer, carbon black, and composite modification additive to a mixer in sequence, stir and mix for 30 minutes, then add stone powder, and continue mixing for 30 minutes to obtain a mixture;

[0055] (3) Banburying: adding the mixed material obtained above into a banbury mixer for banburying treatment to obtain a banburying material;

[0056] Among them, the internal mixing temperature is 200℃;

[0057] The mixing time is 20min;

[0058] (4) Sheeting: Add the mixed material to the calender and press it into a base sheet, and then press the color film onto the base sheet through a press to form a semi-finished product;

[0059] (5) Post-processing: The semi-finished products are subjected to curing, edge punching, laminating, quality inspection, packaging, palletizing and storage.

[0060] The preparation method of the composite modification additive is as follows:

[0061] Firstly, hemicellulose waste alkali liquor, deionized water, modified attapulgite, nano-silicon dioxide and silicon carbide were added to a reactor in sequence, stirred at 500 r / min for 30 min at room temperature, and then ultrasonically dispersed for 1 min to obtain a dispersed mixed solution;

[0062] Sodium bisulfite was added to the dispersed mixed solution obtained above, and the mixture was stirred for reaction for 40 minutes. The reaction temperature was adjusted to 75° C. After the reaction was completed, the mixture was kept warm for 15 minutes to obtain an intermediate solution.

[0063] Add ammonium persulfate to the intermediate solution obtained above, wherein the molar ratio of ammonium persulfate to sodium bisulfite is 1:1, adjust the temperature to 70° C., and stir and react for 40 minutes to obtain a second intermediate solution;

[0064] Adding a mixed solution of n-butyl acrylate and N,N-methylenebisacrylamide dropwise to the second intermediate solution, stirring and reacting for 2 hours, and then filtering to obtain a reaction mixture;

[0065] The reaction mixture is washed with anhydrous ethanol, and then placed in a drying oven for drying to obtain a composite modified auxiliary agent;

[0066] The drying temperature is 60°C and the drying time is 15 hours; the mixing ratio of hemicellulose waste alkali solution, deionized water, modified attapulgite, nano-silicon dioxide and silicon carbide is 120mL: 200mL: 30g: 5g: 1g;

[0067] The hemicellulose concentration is 85 g / L, and the alkali concentration is 28.2 g / L;

[0068] The mixing ratio of the dispersed mixed liquid and sodium bisulfite is 100mL:1g;

[0069] The mass fraction of n-butyl acrylate in the mixed solution of n-butyl acrylate and N,N-methylenebisacrylamide is 10%;

[0070] The mass fraction of N,N-methylenebisacrylamide is 3%;

[0071] The volume ratio of the second intermediate liquid, n-butyl acrylate and N,N-methylenebisacrylamide mixed liquid is 10:1.

[0072] The preparation method of modified attapulgite is as follows:

[0073] The attapulgite and the sulfuric acid solution were mixed, the temperature was adjusted to 80°C, the mixture was stirred for 2 hours, and then allowed to stand for 4 hours, and then filtered, washed with deionized water until neutral, and dried in a drying oven to obtain pretreated attapulgite;

[0074] The pretreated attapulgite was treated with microwaves for 10 minutes and naturally cooled to room temperature to obtain modified attapulgite.

[0075] The concentration of sulfuric acid solution is 2 mol / L;

[0076] The mixing ratio of attapulgite and sulfuric acid solution is 12g:200mL.

[0077] The microwave power is 550W.

[0078] The curing time is 28 hours at a temperature of 25°C.

[0079] Example 2

[0080] A method for preparing a moisture-proof and wear-resistant PVC floor comprises the following steps:

[0081] (1) Material preparation: weigh the raw material components by weight: 62 parts of PVC resin, 5.2 parts of phthalate, 1.5 parts of Ca / Zn stabilizer, 6.5 parts of carbon black powder, 12 parts of composite modification additive, and 80 parts of stone powder;

[0082] (2) Mixing: First, add PVC resin, plasticizer, stabilizer, carbon black, and composite modification additive to a mixer in sequence, stir and mix for 30 minutes, then add stone powder, and continue mixing for 30 minutes to obtain a mixture;

[0083] (3) Banburying: adding the mixed material obtained above into a banbury mixer for banburying treatment to obtain a banburying material;

[0084] Among them, the internal mixing temperature is 200℃;

[0085] The mixing time is 22 minutes;

[0086] (4) Sheeting: Add the mixed material to the calender and press it into a base sheet, and then press the color film onto the base sheet through a press to form a semi-finished product;

[0087] (5) Post-processing: The semi-finished products are subjected to curing, edge punching, laminating, quality inspection, packaging, palletizing and storage.

[0088] The preparation method of the composite modification additive is as follows:

[0089] Firstly, hemicellulose waste alkali liquor, deionized water, modified attapulgite, nano-silicon dioxide and silicon carbide were added to a reactor in sequence, stirred at 500 r / min for 30 min at room temperature, and then ultrasonically dispersed for 1 min to obtain a dispersed mixed solution;

[0090] Sodium bisulfite was added to the dispersed mixed solution obtained above, and the mixture was stirred for reaction for 40 minutes. The reaction temperature was adjusted to 75° C. After the reaction was completed, the mixture was kept warm for 15 minutes to obtain an intermediate solution.

[0091] Add ammonium persulfate to the intermediate solution obtained above, wherein the molar ratio of ammonium persulfate to sodium bisulfite is 1:1, adjust the temperature to 70° C., and stir and react for 40 minutes to obtain a second intermediate solution;

[0092] Adding a mixed solution of n-butyl acrylate and N,N-methylenebisacrylamide dropwise to the second intermediate solution, stirring and reacting for 2 hours, and then filtering to obtain a reaction mixture;

[0093] The reaction mixture is washed with anhydrous ethanol, and then placed in a drying oven for drying to obtain a composite modified auxiliary agent;

[0094] The drying temperature is 60°C and the drying time is 15 hours; the mixing ratio of hemicellulose waste alkali solution, deionized water, modified attapulgite, nano-silicon dioxide and silicon carbide is 120mL: 200mL: 32g: 6g: 1.2g;

[0095] The hemicellulose concentration is 85 g / L, and the alkali concentration is 28.2 g / L;

[0096] The mixing ratio of the dispersed mixed liquid and sodium bisulfite is 100mL:1.5g;

[0097] The mass fraction of n-butyl acrylate in the mixed solution of n-butyl acrylate and N,N-methylenebisacrylamide is 10%;

[0098] The mass fraction of N,N-methylenebisacrylamide is 3%;

[0099] The volume ratio of the second intermediate liquid, n-butyl acrylate and N,N-methylenebisacrylamide mixed liquid is 10:1.1.

[0100] The preparation method of modified attapulgite is as follows:

[0101] The attapulgite and the sulfuric acid solution were mixed, the temperature was adjusted to 80°C, the mixture was stirred for 2 hours, and then allowed to stand for 4 hours, and then filtered, washed with deionized water until neutral, and dried in a drying oven to obtain pretreated attapulgite;

[0102] The pretreated attapulgite was treated with microwaves for 12 minutes and naturally cooled to room temperature to obtain modified attapulgite.

[0103] The concentration of sulfuric acid solution is 2 mol / L;

[0104] The mixing ratio of attapulgite and sulfuric acid solution is 13g:200mL.

[0105] The microwave power is 550W.

[0106] The curing time is 28-30 hours at a temperature of 25°C.

[0107] Example 3

[0108] A method for preparing a moisture-proof and wear-resistant PVC floor comprises the following steps:

[0109] (1) Material preparation: weigh the raw material components by weight, including: 65 parts of PVC resin, 5.5 parts of phthalate, 2 parts of Ca / Zn stabilizer, 6.5 parts of carbon black powder, 13 parts of composite modification additive, and 80 parts of stone powder;

[0110] (2) Mixing: First, add PVC resin, plasticizer, stabilizer, carbon black, and composite modification additive to a mixer in sequence, stir and mix for 30 minutes, then add stone powder, and continue mixing for 30 minutes to obtain a mixture;

[0111] (3) Banburying: adding the mixed material obtained above into a banbury mixer for banburying treatment to obtain a banburying material;

[0112] Among them, the internal mixing temperature is 200℃;

[0113] The mixing time is 20min;

[0114] (4) Sheeting: Add the mixed material to the calender and press it into a base sheet, and then press the color film onto the base sheet through a press to form a semi-finished product;

[0115] (5) Post-processing: The semi-finished products are subjected to curing, edge punching, laminating, quality inspection, packaging, palletizing and storage.

[0116] The preparation method of the composite modification additive is as follows:

[0117] Firstly, hemicellulose waste alkali liquor, deionized water, modified attapulgite, nano-silicon dioxide and silicon carbide were added to a reactor in sequence, stirred at 500 r / min for 30 min at room temperature, and then ultrasonically dispersed for 1 min to obtain a dispersed mixed solution;

[0118] Sodium bisulfite was added to the dispersed mixed solution obtained above, and the mixture was stirred for reaction for 40 minutes. The reaction temperature was adjusted to 75° C. After the reaction was completed, the mixture was kept warm for 15 minutes to obtain an intermediate solution.

[0119] Add ammonium persulfate to the intermediate solution obtained above, wherein the molar ratio of ammonium persulfate to sodium bisulfite is 1:1, adjust the temperature to 70° C., and stir and react for 40 minutes to obtain a second intermediate solution;

[0120] Adding a mixed solution of n-butyl acrylate and N,N-methylenebisacrylamide dropwise to the second intermediate solution, stirring and reacting for 2 hours, and then filtering to obtain a reaction mixture;

[0121] The reaction mixture is washed with anhydrous ethanol, and then placed in a drying oven for drying to obtain a composite modified auxiliary agent;

[0122] The drying temperature is 60°C and the drying time is 15 hours; the mixing ratio of hemicellulose waste alkali solution, deionized water, modified attapulgite, nano-silicon dioxide and silicon carbide is 120mL: 200mL: 32g: 6g: 1.2;

[0123] The hemicellulose concentration is 85 g / L, and the alkali concentration is 28.2 g / L;

[0124] The mixing ratio of the dispersed mixed liquid and sodium bisulfite is 100mL:1.5g;

[0125] The mass fraction of n-butyl acrylate in the mixed solution of n-butyl acrylate and N,N-methylenebisacrylamide is 10%;

[0126] The mass fraction of N,N-methylenebisacrylamide is 3%;

[0127] The volume ratio of the second intermediate liquid, n-butyl acrylate and N,N-methylenebisacrylamide mixed liquid is 10:1.

[0128] The preparation method of modified attapulgite is as follows:

[0129] The attapulgite and the sulfuric acid solution were mixed, the temperature was adjusted to 80°C, the mixture was stirred for 2 hours, and then allowed to stand for 4 hours, and then filtered, washed with deionized water until neutral, and dried in a drying oven to obtain pretreated attapulgite;

[0130] The pretreated attapulgite was treated with microwaves for 12 minutes and naturally cooled to room temperature to obtain modified attapulgite.

[0131] The concentration of sulfuric acid solution is 2 mol / L;

[0132] The mixing ratio of attapulgite and sulfuric acid solution is 13g:200mL.

[0133] The microwave power is 550W.

[0134] The curing time is 28 hours at a temperature of 25°C.

[0135] Example 4

[0136] A method for preparing a moisture-proof and wear-resistant PVC floor comprises the following steps:

[0137] (1) Material preparation: weigh the raw material components by weight, including: 66 parts of PVC resin, 6 parts of phthalate, 2 parts of Ca / Zn stabilizer, 7 parts of carbon black powder, 14 parts of composite modification additive, and 83 parts of stone powder;

[0138] (2) Mixing: First, add PVC resin, plasticizer, stabilizer, carbon black, and composite modification additive to a mixer in sequence, stir and mix for 30 minutes, then add stone powder, and continue mixing for 30 minutes to obtain a mixture;

[0139] (3) Banburying: adding the mixed material obtained above into a banbury mixer for banburying treatment to obtain a banburying material;

[0140] Among them, the internal mixing temperature is 200℃;

[0141] The mixing time is 25min;

[0142] (4) Sheeting: Add the mixed material to the calender and press it into a base sheet, and then press the color film onto the base sheet through a press to form a semi-finished product;

[0143] (5) Post-processing: The semi-finished products are subjected to curing, edge punching, laminating, quality inspection, packaging, palletizing and storage.

[0144] The preparation method of the composite modification additive is as follows:

[0145] Firstly, hemicellulose waste alkali liquor, deionized water, modified attapulgite, nano-silicon dioxide and silicon carbide were added to a reactor in sequence, stirred at 500 r / min for 30 min at room temperature, and then ultrasonically dispersed for 1 min to obtain a dispersed mixed solution;

[0146] Sodium bisulfite was added to the dispersed mixed solution obtained above, and the mixture was stirred for reaction for 40 minutes. The reaction temperature was adjusted to 75° C. After the reaction was completed, the mixture was kept warm for 15 minutes to obtain an intermediate solution.

[0147] Add ammonium persulfate to the intermediate solution obtained above, wherein the molar ratio of ammonium persulfate to sodium bisulfite is 1:1, adjust the temperature to 70° C., and stir and react for 40 minutes to obtain a second intermediate solution;

[0148] Adding a mixed solution of n-butyl acrylate and N,N-methylenebisacrylamide dropwise to the second intermediate solution, stirring and reacting for 2 hours, and then filtering to obtain a reaction mixture;

[0149] The reaction mixture is washed with anhydrous ethanol, and then placed in a drying oven for drying to obtain a composite modified auxiliary agent;

[0150] The drying temperature is 60°C and the drying time is 15 hours; the mixing ratio of hemicellulose waste alkali solution, deionized water, modified attapulgite, nano-silicon dioxide and silicon carbide is 120mL: 200mL: 33g: 7g: 1.5g;

[0151] The hemicellulose concentration is 85 g / L, and the alkali concentration is 28.2 g / L;

[0152] The mixing ratio of the dispersed mixed liquid and sodium bisulfite is 100mL:1.5g;

[0153] The mass fraction of n-butyl acrylate in the mixed solution of n-butyl acrylate and N,N-methylenebisacrylamide is 10%;

[0154] The mass fraction of N,N-methylenebisacrylamide is 3%;

[0155] The volume ratio of the second intermediate liquid, n-butyl acrylate and N,N-methylenebisacrylamide mixed liquid is 10:1.

[0156] The preparation method of modified attapulgite is as follows:

[0157] The attapulgite and the sulfuric acid solution were mixed, the temperature was adjusted to 80°C, the mixture was stirred for 2 hours, and then allowed to stand for 4 hours, and then filtered, washed with deionized water until neutral, and dried in a drying oven to obtain pretreated attapulgite;

[0158] The pretreated attapulgite was treated with microwaves for 12 minutes and naturally cooled to room temperature to obtain modified attapulgite.

[0159] The concentration of sulfuric acid solution is 2 mol / L;

[0160] The mixing ratio of attapulgite and sulfuric acid solution is 15g:200mL.

[0161] The microwave power is 550W.

[0162] The curing time is 29 hours at a temperature of 25°C.

[0163] Comparative Example 1:

[0164] On the basis of Example 1, no composite modification additive is added, and the remaining technical solutions are as follows.

[0165] Comparative Example 2:

[0166] On the basis of Example 1, when preparing the composite modification auxiliary agent, the attapulgite is not modified, and the remaining technical schemes are as follows.

[0167] test:

[0168] According to the methods of the embodiments and comparative examples, 30 mm × 30 mm × 2 mm samples were prepared for testing;

[0169] The density of the sample was determined according to the immersion method specified in GB / T 1033.1.

[0170] Table 1

[0171] <![CDATA[Density g / cm 3 > Example 1 1.205 Example 2 1.222 Example 3 1.268 Example 4 1.289

[0172] It can be seen from Table 1 that the PVC floor prepared by the present invention has a suitable density, which is relatively low. Under the same volume, the weight is lighter than that of the floor made of templates and ceramic materials.

[0173] According to the "Determination of Tensile Properties of Plastics Part 1: General Principles" (GB / T1040.1-2018), the tensile strength of the examples and comparative examples is tested;

[0174] Table 2

[0175] Tensile strength MPa Example 1 11.89 Example 2 12.36 Example 3 12.05 Example 4 11.93 Comparative Example 1 8.62 Comparative Example 2 9.88

[0176] It can be seen from Table 2 that the PVC floor of the present invention has excellent mechanical properties, especially the tensile strength is significantly improved.

[0177] Mass loss at 5500 rpm

[0178] The Taber type wear tester rotates (65±1) revolutions per minute; the samples of the embodiment and the comparative example are installed on the wear tester, the dust suction device is turned on, and the wear is carried out under the condition of applying an external force of 5.0N±0.1N, and the wear is carried out for 5500 revolutions. After weighing, the wear resistance revolution test is continued.

[0179] Table 3

[0180]

[0181]

[0182] It can be seen from Table 3 that the PVC floor prepared by the present invention has excellent wear resistance. The above is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made according to the concept of the present invention, or modified into equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.

Claims

1. A method for preparing a moisture-proof and wear-resistant PVC floor, characterized in that: The following steps are involved: (1) Material preparation: weigh the raw material components: PVC resin, plasticizer, stabilizer, carbon black, composite modification additive, stone powder; (2) Mixing: First, add PVC resin, plasticizer, stabilizer, carbon black, and composite modification additive to the mixer in sequence, stir and mix for 30 minutes, then add stone powder, and continue mixing for 30 minutes to obtain a mixture; (3) Banburying: adding the mixed material obtained above into a banbury mixer for banburying treatment to obtain a banburying material; Among them, the internal mixing temperature is 200℃; The mixing time is 20-25 minutes; (4) Sheeting: Add the mixed material to the calender and press it into a base sheet, and then use a press to press the color film onto the base sheet to form a semi-finished product; (5) Post-processing: the semi-finished products are subjected to curing, edge punching, laminating, quality inspection, packaging, palletizing and storage; The preparation method of the composite modification auxiliary agent in step (1) is: Firstly, hemicellulose waste alkali liquor, deionized water, modified attapulgite, nano-silicon dioxide and silicon carbide were added to a reactor in sequence, stirred at 500 r / min for 30 min at room temperature, and then ultrasonically dispersed for 1 min to obtain a dispersed mixed solution; Sodium bisulfite was added to the dispersed mixed solution obtained above, and the mixture was stirred for reaction for 40 minutes. The reaction temperature was adjusted to 75° C. After the reaction was completed, the mixture was kept warm for 15 minutes to obtain an intermediate solution. Add ammonium persulfate to the intermediate solution obtained above, wherein the molar ratio of ammonium persulfate to sodium bisulfite is 1:1, adjust the temperature to 70° C., and stir and react for 40 minutes to obtain a second intermediate solution; Adding a mixed solution of n-butyl acrylate and N,N-methylenebisacrylamide dropwise to the second intermediate solution, stirring and reacting for 2 hours, and then filtering to obtain a reaction mixture; The reaction mixture is washed with anhydrous ethanol, and then placed in a drying oven for drying to obtain a composite modified auxiliary agent; The drying temperature is 60°C and the drying time is 15 hours; The modified attapulgite preparation method is: The attapulgite and the acid treatment solution were mixed, the temperature was adjusted to 80°C, the mixture was stirred for 2 hours, and then allowed to stand for 4 hours, and then filtered, washed with deionized water until neutral, and dried in a drying oven to obtain pretreated attapulgite; The pretreated attapulgite was treated with microwaves for 10-15 minutes and naturally cooled to room temperature to obtain modified attapulgite.

2. The method for preparing a moisture-proof and wear-resistant PVC floor according to claim 1, characterized in that: The raw material components in step (1) include, by weight: 60-68 parts of PVC resin, 5-6 parts of plasticizer, 1-3 parts of stabilizer, 6-8 parts of carbon black powder, 10-15 parts of composite modification additive, and 78-85 parts of stone powder.

3. The method for preparing a moisture-proof and wear-resistant PVC floor according to claim 1, characterized in that: The mixing ratio of the hemicellulose waste alkali solution, deionized water, modified attapulgite, nano silicon dioxide and silicon carbide is 120 mL: 200 mL: 30-35 g: 5-8 g: 1-1.5 g; The hemicellulose concentration: 85g / L, alkali concentration: 28.2g / L; The mixing ratio of the dispersed mixed liquid and sodium bisulfite is 100mL: 1-2g; The mass fraction of n-butyl acrylate in the mixed solution of n-butyl acrylate and N,N-methylenebisacrylamide is 10%; The mass fraction of N,N-methylenebisacrylamide is 3%; The volume ratio of the second intermediate liquid, n-butyl acrylate and N,N-methylenebisacrylamide mixed liquid is 10:1-1.

2.

4. The method for preparing a moisture-proof and wear-resistant PVC floor according to claim 1, characterized in that: The acid treatment solution is a sulfuric acid solution; The concentration of the sulfuric acid solution is 2 mol / L; The mixing ratio of attapulgite and sulfuric acid solution is 12-16g:200mL.

5. The method for preparing a moisture-proof and wear-resistant PVC floor according to claim 1, characterized in that: The microwave power is 550W.

6. The method for preparing a moisture-proof and wear-resistant PVC floor according to claim 1, characterized in that: The plasticizer is phthalate.

7. The method for preparing a moisture-proof and wear-resistant PVC floor according to claim 1, characterized in that: The stabilizer is a Ca / Zn stabilizer.

8. The method for preparing a moisture-proof and wear-resistant PVC floor according to claim 1, characterized in that: The curing time is 28-30 hours, and the temperature is 25°C.

Citation Information

Patent Citations

  • Semi-flexible polyvinyl chloride (PVC) floor

    CN102345368A

  • Cross-linked dynamic polymer and application thereof

    CN108341965A

  • A preparing method of wear-resistant artificial leather

    CN109551850A